Comparative Testing of Experts - Al-Najjar, Nabil I.; Weinstein, Jonathan (Econometrica, 2008)
We show that a simple "reputation-style" test can always identify which of two experts is informed about the true distribution. The test presumes no prior knowledge of the true distribution, achieves any desired degree of precision in some fixed finite time, and does not use "counterfactual" predictions. Our analysis capitalizes on a result of Fudenberg and Levine (1992) on the rate of convergence of supermartingales. Copyright Copyright 2008 by The Econometric Society.